Removal Efficiency of Cr6+ by Indigenous Pichia sp. Isolated from Textile Factory Effluent - Pablo M. Fernández; María M. Martorell; Julia I. Fariña; Lucia I. C. Figueroa (The Scientific World Journal)
Resistance of the indigenous strains P. jadinii M9 and P. anomala M10, to high Cr6+ concentrations and their ability to reduce chromium in culture medium was studied. The isolates were able to tolerate chromium concentrations up to 104 μg mL−1. Growth and reduction of Cr6+ were dependent on incubation temperature, agitation, Cr6+ concentration, and pH. Thus, in both studied strains the chromium removal was increased at 30°C with agitation. The optimum pH was different, with values of pH 3.0 and pH 7.0 in the case of P. anomala M10 and pH 7.0 using P. jadinii M9. Chromate reduction occurred both in intact cells (grown in culture medium) as well as in cell-free extracts. Chromate reductase activity could be related to cytosolic or membrane-associated proteins. The presence of a chromate reductase activity points out a possible role of an enzyme in Cr6+ reduction.